A Study of Online Shopping Behavior among Home Makers in India - Khan, Eisha (International Journal of Advanced Science and Technology, 2019)
The objective of the present study is to find out the factors affecting the online shopping behavior of female shoppers in India and to understand the relationship between the satisfaction and loyalty in context of female shoppers in India.The survey was conducted using a close ended questionnaire distributed online to the online shoppers and data was collected from 234 online female shoppers.The data was analyzed by statistical techniques CFA and SEM.The results of the study concluded the customer service and innovation are the important factor which leads to loyalty development among the female online shoppers .The following results can be used by the marketers to have a better understanding of online consumer behavior of female shoppers in India